2011
DOI: 10.1002/cncr.26445
|View full text |Cite
|
Sign up to set email alerts
|

11C‐methionine uptake and intraoperative 5‐aminolevulinic acid‐induced fluorescence as separate index markers of cell density in glioma

Abstract: BACKGROUND:The extent of tumor resection is acknowledged as 1 of the prognostic factors for glioma. 5-Aminolevulinic acid (5-ALA)-induced fluorescence guidance and neuronavigation integrated with 11 C-methionine positron emission tomography (PET) are widely utilized under the expectation of improving the extent of resection. These 2 novel approaches are beneficial for glioma resections, and the combination of these approaches appears rational. However, biological characteristics reflecting 5-ALA-induced fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 40 publications
(85 reference statements)
2
34
0
Order By: Relevance
“…18 Higher levels of fluorescence have higher levels of ALA-induced protoporphyrin concentration and correlate strongly with increasing malignancy (histopathological score) and tissue proliferation. 2,31 To our knowledge, there are only 2 studies that have directly addressed the relationship of intraoperative ALA fluorescence intensity with degree of cellularity.…”
Section: Discussionmentioning
confidence: 99%
“…18 Higher levels of fluorescence have higher levels of ALA-induced protoporphyrin concentration and correlate strongly with increasing malignancy (histopathological score) and tissue proliferation. 2,31 To our knowledge, there are only 2 studies that have directly addressed the relationship of intraoperative ALA fluorescence intensity with degree of cellularity.…”
Section: Discussionmentioning
confidence: 99%
“…Because the amount of accumulated 11 C-methionine is correlated with the amount of amino acid transporters within the lesion, the magnitude of 11 C-methionine accumulation shows a positive correlation with glioma cell density (7). Our previous reports have suggested that this assumption is true to some extent in both tumor-core and tumor-infiltrative lesions, making 11 Cmethionine PET a reliable imaging modality for glioma cell detection (5,6). This correlation, however, is not well preserved in tumor-infiltrative lesions (5).…”
Section: Discussionmentioning
confidence: 99%
“…Different imaging methods, such as diffusion tensor MRI (DTI) and amino acid PET, have been proposed to overcome this issue (1)(2)(3)(5)(6)(7). The ability of these 2 imaging modalities to characterize microstructural and metabolic tissue information has led to their use for glioma imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies were undertaken to detect regions of ALA-induced PpIX accumulation in malignant tumors with noninvasive tomographic imaging such as gadolinium-enhanced MR imaging (14) or PET with L-[methyl-11 C]-methionine ( 11 C-MET) (15) (12). Those studies showed that there were some differences between gadoliniumenhanced MR imaging or 11 C-MET or 18 F-FET PET imaging and PpIX accumulation (12,15), because these diagnostic images provided information different from PpIX accumulation-that is, gadolinium-enhanced MR imaging and PET with 11 C-MET or 18 F-FET reflect the blood-brain barrier breakdown (16) or amino acid metabolism (17) but not PpIX accumulation. Therefore, a new noninvasive imaging method based on the mechanism of PpIX accumulation is needed.…”
mentioning
confidence: 99%